The Urgency of Registering Marriage for Men During the Syibhul 'Iddah Period Based on the Theory of Maʿālāt al-Afʿāl : Urgensi Pencatatan Nikah Lelaki Dalam Masa Syibhul ‘Iddah Berdasar Teori Maʿālāt al-Afʿāl - Muhammad Subhan; Nelli Jumni (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Marriage registration constitutes a fundamental component of Islamic family law and national legal administration, particularly in regulating post-divorce marital status and preventing social disorder. Specific Background: In Indonesia, debates arise concerning men who intend to remarry while their former wives are still in the ʿiddah period, a condition described as syibhul ‘iddah, especially following the Circular Letter of the Director General of Islamic Community Guidance No. P-005/DJ.III/HK.00.7/10/2021. Knowledge Gap: Although classical fiqh strictly regulates women’s ʿiddah, no explicit sharʿi prohibition governs men outside specific maniʿ syarʿi cases, creating a normative and administrative vacuum regarding male marriage registration during syibhul ‘iddah. Aims: This study examines the urgency and juridical basis for registering marriages of men in the syibhul ‘iddah condition through the theory of Maʿālāt al-Afʿāl and a maqāṣid al-sharīʿah approach. Results: Using normative qualitative analysis, the findings indicate that Maʿālāt al-Afʿāl permits administrative discretion when dominant maslahat is evident and potential mafsadat—such as unregistered marriage, social conflict, or moral transgression—can be prevented, provided careful verification procedures are applied. Novelty: The study demonstrates how Maʿālāt al-Afʿāl functions as a doctrinal framework to legitimize contextual administrative reinterpretation without contravening Islamic law or the national legal system. Implications: Adaptive policy formulation grounded in maqāṣid al-sharīʿah may reconcile Islamic jurisprudence and positive law, ensuring legal certainty, social order, and prevention of greater harm in specific divorce cases. Highlights: Administrative discretion may be justified when dominant maslahat outweighs potential mafsadat in specific divorce contexts. Normative analysis confirms no explicit sharʿi prohibition for men outside defined maniʿ syarʿi situations. Policy adaptation can align jurisprudential objectives with national legal administration through careful verification mechanisms. Keywords: Male Mattiage Registration, Syibhul ‘Iddah, Theory of Maʿālāt Al-Afʿāl